Shedding the Light on the Off-Hours Problem in Radiology. (September 2020) - Roth, Christopher G.; Boroumand, Gilda; Dave, Jaydev K.
Diagnostic error and diagnostic delays in health care are widespread. This article outlines an improvement effort targeting weekday evening inpatient radiology delays through staffing changes replacing trainees with faculty-trainee team coverage, pushing faculty coverage from 4pm to 8pm . Order-report turnaround times (TATs), critical findings TATs for pneumothorax and intracranial hemorrhage (ICH), and percentage meeting target were compared pre and post implementation for the 4 to 8pm time frame using the Mann-Whitney U and χ 2 tests, respectively. Stakeholder surveys assessed patient safety, morale, education, and operational efficiency. Median TATs (minutes) improved: X-rays 906 to 112, computed tomography 994 to 84, magnetic resonance imaging 1172 to 233, and ultrasound 88 to 58. Median critical findings TATs (minutes) improved from 853 to 30 and 112 to 22 for pneumothorax and ICH, respectively, and the percentage meeting target improved from 45% to 65%. Survey results reported perceived improvement in patient safety, education, and operational efficiency and no impact on morale.